Answers

2014-11-05T17:48:33+05:30
(a+b+c)*(a+b+c)*(a+b+c) = (a to the power 3+ b to the power 3+ c to the power 3) =(a+b+c) to the power 3 =(a+b+c) cube
0
2014-11-05T17:53:42+05:30
(a+b+c) * ( a + b + c) * ( a + b + c)= (a+b +c)^3
since we can use the power of exponent rule of a^m * a^n = a^ m+n.
like that in the above problem the powers are as (a+b+c)^1 , so as per the rule we did it as (a +b+c)^3. we can expand it as (a+b+c)^2 * (a+b+c)
so we know the formula for (a +b +c )^2 = a^2 +b^2 +c ^2 + 2 ab + 2bc +2ca 
(a^2 +b^2 +c ^2 + 2 ab + 2bc +2ca) (a+b+c) 

0